"When the rainbow is enuf" : black postgraduate women's experiences and perceptions of higher education and institutional culture "“ a case study of Rhodes University - Gamedze, Ayanda (Rhodes University, Faculty of Humanities, Department of Sociology, 2020)
This thesis sets out to investigate the perceptions which Black postgraduate students hold of the present-day toward Historically White Universities (hereafter referred to as HWUs) in South Africa as unique sites from which to investigate institutional culture and the legacy of educational marginalisation. Black women are of particular focus because of the interlocking nature of social inequalities that uniquely influence their comparable experience in the academy. Rhodes University, a top-ranked traditional university provides the institutional site for this investigation into HWUs. This thesis seeks to further explore the suggestion that desegregation of South Africa's institutions of higher learning have meant access, but not always acceptance. The paper explores what Black women students perceive to be Rhodes University's institutional culture and its impact on their lived realities. Subsequently, these women have learned who they are, and what place they occupy in South Africa today, through navigating a space not necessarily accommodating to Blackness and difference. There exists a plethora of literature on the issues which Black women scholars systematically encounter daily in the academy, in sub-Saharan Africa and beyond. Nonetheless, there needs to be a further inquiry on the question of belonging of Black womanhood in HWU post the student-led movements of the past few years that have renewed the challenge to South Africa's colonial past, its neoliberal present, and its scourge of gender-based violence. This paper captures an ongoing conversation around the role of Black women in addressing transformation in HWU. As a Black woman in an HWU, I found myself wondering whether there are certain experiences students like me have in common "“ realities with nuances we call to identify with to some extent. I collected data from six Black women with whom I conducted interviews, and used it to compile this report and its analysis. I believe that the social significance of this study speaks to the importance of hearing the stories of subaltern groups that are positioned in spaces of privilege, yet continue to be defined by the disadvantage of their gender, race, and various other factors.
Keywords: Rhodes University; College students, Black -- South Afrca; Women college students, Black -- South Africa